The efficacy and safety of combining different Chinese patent medicines with conventional Western drugs in the treatment of pediatric allergic rhinitis: network meta-analysis - Ma, Yue; Huang, Wenrui; Wu, Hang; Zhang, Chunbo; Xiao, Zhiyue; Gao, Yuying; Xie, Junying; Xu, Jingyao (Frontiers in Pharmacology, 2025)
Ethnopharmacological SignificancePediatric allergic rhinitis (AR) is often treated with conventional Western medical therapy (CWMT), but such regimens can cause adverse effects. Evidence suggests that Chinese patent medicines (CPMs) combined with CWMT may improve symptom control and immunological markers, yet no PRISMA-compliant network meta-analysis (NMA) has systematically compared available CPMs.ObjectiveThis study aims to conduct an NMA of randomised controlled trials (RCTs) comparing the efficacy and safety of CPMs plus CWMT in pediatric AR.MethodsWe conducted a PRISMA-guided NMA of randomized controlled trials evaluating CPMs plus CWMT versus CWMT alone for pediatric allergic rhinitis. Eight databases were searched through May 2025. Risk of bias was assessed using the Cochrane Risk of Bias 2.0 tool, and evidence certainty was graded using the Confidence in Network Meta-Analysis (CINeMA) framework. Continuous outcomes were expressed as standardized mean differences (SMDs) with 95% confidence intervals (CIs), while binary outcomes were summarized as odds ratios (ORs) or risk ratios (RRs) with corresponding 95% CIs. Analyses were performed in StataMP 18, and treatment hierarchies were ranked using the surface under the cumulative ranking curve (SUCRA) method.ResultsA total of 49 RCTs involving 5,062 participants and 13 CPMs were included. Compared with CWMT alone, the combination of CPMs and CWMT significantly improved the Total Nasal Symptom Score (TNSS). Tongqiao Biyan Granules (TBG) achieved the greatest improvements across nasal obstruction (SMD = −1.79, 95% CI: −2.84 to −0.74; SUCRA 72.3%), sneezing (SMD = −2.09, 95% CI: −3.27 to −0.91; SUCRA 78.8%), and rhinorrhea (SMD = −1.88, 95% CI: −3.20 to −0.56; SUCRA 78.2%), indicating consistent superiority over other regimens, and Sanfeng Tongqiao Dropping Pills (STDP) being most effective for nasal pruritus (SMD = −1.57; SUCRA 81.9%). For overall efficacy, all CPM combinations outperformed CWMT, with Cang’er Zibi Yan Pills (CBP) achieving the highest improvement (RR = 1.25, 95% CI: 1.06–1.49; SUCRA 77.2%). Although seven CPMs showed a trend toward reduced serum IgE, none reached statistical significance; Xinqin Granules (XG) ranked highest (SUCRA 76.9%). Adverse events were generally mild and less frequent with combination therapy, with Yuping Feng Granules (YG) showing the lowest risk (OR = 0.33, 95% CI: 0.19–0.55 SUCRA 79.5%). Recurrence analysis (18 trials, 1,511 participants) indicated that most CPM combinations lowered relapse risk, with Huaiqi Huang Granules (HG) performing best (OR = 0.24, 95% CI: 0.06–0.92; SUCRA 84.8%). Sensitivity and meta-regression analyses confirmed the robustness of these findings, and all significant TNSS improvements exceeded the minimal clinically important difference (MCID = 0.55), indicating clinically meaningful symptom relief.ConclusionCombining CPMs with CWMT may offer superior efficacy and safety for pediatric AR. These findings support CPMs as an adjunct to standard therapy, though large, high-quality RCTs are warranted for confirmation.Systematic Review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251080593.